Adaptive Logics for Abduction and the Explication of Explanation-Seeking Processes - Meheus, Joke (Abduction and the Process of Scientific Discovery, 2007)
In this paper, I illustrate the main characteristics of abductive reasoning processes by means of an example from the history of the sciences. The example is taken from the history of chemistry and concerns a very small episode from Lavoisiers struggle with the air obtained from mercury oxide. Eventually, this struggle would lead to the discovery of oxygen. I also show that Lavoisiers reasoning process can be explicated by means of a particular formal logic, namely the adaptive logic LAr. An important property of LAr is that it not only nicely integrates deductive and abductive steps, but that it moreover has a decent proof theory. This proof theory is dynamic, but warrants that the conclusions derived at a given stage are justified in view of the insight in the premises at that stage. Another advantage of the presented logic is that, as compared to other existing systems for abductive reasoning, it is very close to natural reasoning.